2023
DOI: 10.3389/fncel.2022.1094291
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrogenesis and myelination tracing in a CRISPR/Cas9-engineered brain microphysiological system

Abstract: IntroductionOligodendrocytes (OLs) are the myelin-forming cells of the central nervous system (CNS). Although OLs can be differentiated from human-induced pluripotent stem cells (hiPSCs), the in vitro modeling of axon myelination in human cells remains challenging. Brain microphysiological systems (bMPS, e.g. organoids) are complex three-dimensional (3D) cultures that offer an ideal system to study this process as OLs differentiate in a more in vivo-like environment; surrounded by neurons and astrocytes, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…An advantage of GEM over commercial media is that the key factors driving and enhancing the glial populations are known and can be easily modified to tailor culture needs. We previously showed that Neurobasal Plus medium in combination with B27 plus supplement also increased the glial populations in comparison to the Electrophysiology kit (23), however an advantage of GEM is that cultures can be modulated in a more flexible manner than when proprietary formulations are used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An advantage of GEM over commercial media is that the key factors driving and enhancing the glial populations are known and can be easily modified to tailor culture needs. We previously showed that Neurobasal Plus medium in combination with B27 plus supplement also increased the glial populations in comparison to the Electrophysiology kit (23), however an advantage of GEM is that cultures can be modulated in a more flexible manner than when proprietary formulations are used.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, hiPSCs and hESCs were cultured in mTESR-Plus medium (StemCell Technologies at 5% O 2 , 5% CO 2 and 37 °C). The cells were characterized based on expression of stemness markers (Oct4, Nanog and TRA-1-60) by flow cytometry (iPSC characterization see Romero et al, 2023(23), ESC characterization is summarized in Supplemental Figures 1 and 2). Stem cells were then differentiated in a monolayer to neuroprogenitor cells (NPCs) using a serum-free, chemically defined neural induction medium (Gibco, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Smirnova showed how, oligodendrogenesis can be quantified in response to different stimuli using a CRISPR-Cas9-engineered GFP-PLP1 reporter line (Romero et al, 2023). Smirnova's group is currently working on the implementation of a microfluidic system to increase perfusion and biomass (for energy efficiency in biocomputing), as well as biocomplexity.…”
Section: Brain Organoids Track Introductionmentioning
confidence: 99%